Studying Stability of a Non-linear Autoregressive Model - Anas Salim Youns; Abdul Ghafoor Jasim Salim (College of Education for Pure Sciences, 2018)
In this paper we study the stability of one non-linear autoregressive model with hyperbolic triangle function polynomial with hyperbolic tangent function (singular point and it's stability conditions and the stability of the limit cycle) by using the local linearization approximation method and we apply this theory results by using some of examples to explain that.